Marriage Settlement among Minority Moslem by Datok Imam Masjid in South Thailand - Umi Supraptiningsih; Khoirul Bariyyah (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2019)
Thailand is a Moslem minority country with most of Moslem community centered at the plateu of its South area. As the minority, they can not perform sharia laws formally under official acknowledgment. Therefore, in dealing with any law practice, particularly marriage settlement, they rely on the rules of fiqh school followed by each local Datok Imam Masjid. The Datok himself exists in every village even subvillage and is a delegation from the Commitee of Islam at Province serving to deal with any religious affairs. However, The Commitee does not arrange particular rules in the marriage settlement so the practice is fully guided and handled by the Datok. On the basis of that, this research would like to use a qualitative approach through descriptive method. It is found that the principles and requirements of marriage settlement are in line with common Islamic laws as stated in the Qur’an and hadith. Most of the Datok in the South Thailand serving as penghulu (staffs of marriage settlement) affiliate to Shafi’i school. However, as each datok has different views and beliefs on certain issues, the rules become too flexible such as in the matter of minimum age for the brides and bridegrooms or the existence of walī (Islamic guardian mainly from family line) as the marriage requirement. Additionally, the marriage settlement with a newly converted Moslem and “free” polygamy also become big issues as there found no exact rule governing all the details. The settlement is also often hard to hold due to the expensive request of mahr (dowry) which cause the high number of eloping cases as the consequence. (Minoritas Muslim di Thailand Selatan Dataran Tinggi merupakan wilayah yang tidak mendapat kesempatan untuk melaksanakan hukum syari’ah secara resmi yang dapat diakui oleh negara. Oleh karenanya, pelaksanaan pernikahan bagi minoritas Muslim di Thailand Selatan ini masih menggunakan peraturan sesuai dengan mazhab masing-masing yang diurus oleh Datok Imam Masjid di setiap kampung. Datok Imam Masjid tersebut merupakan utusan dari Komite Islam Provinsiyang berwenang mengurus segala bentuk urusan keagamaan khususnya Islam. Walaupun begitu, Komite Islam di Thailand tidak memiliki aturan yang pasti tentang pelaksanaan perikahan sehingga aturan dari pelaksanaan pernikahan tersebut diserahkan sepenuhnya kepada Datok Imam Masjid. Berdasarkan hal tersebut, maka tujuan dari penelitian ini adalah untuk mengetahui bagaimana pelaksanaan pernikahan bagi minoritas Muslim di Thailand Selatan dan kajian hukum Islam tentang pelaksanaan pernikahan tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan jenis deskriptif. Dari hasil penelitian didapatkan bahwa, rukun dalam pelaksanaan pernikahan sudah sesuai dengan hukum Islam. Pada umumnya Datok Imam Masjid di Thailand Selatan yang menjadi juru nikah menggunakan mazhab Syafi’i, namun adanya perbedaan pengetahuan agama pada setiap Datok Imam Masjid menyebabkan longgarnya aturan-aturan yang digunakan dalam pelaksanaan pernikahan, seperti halnya syarat usia calon mempelai dan penggunaan wali hakim dalam pernikahan, pernikahan dengan muallaf tanpa adanya perhatian khusus serta maraknya pernikahan poligami tanpa adanya batasan-batasan tertentu. Selain itu, pelaksanaan pernikahan seringkali terhambat oleh adanya permintaan jumlah mahar yang tinggi dari pihak perempuan yang menyebabkan banyaknya kasus kawin lari)